To the question about the lexico-semantic filling of the word-formation paradigm of emotional state verbs in the Russian language - Tretsiakova, Yuliya R. (Journal of the Belarusian State University. Philology, 2022)
The guiding principle of the research in the field of language in modern linguistics is the theory of the systemic organisation of language and, consequently, of all its levels. This article is devoted to the word-formation paradigm as a microsystem built on the relations of derivation and capable of acting in specific and typical forms of functioning. The paper presents a typical derivational paradigm of emotional state verbs in Russian. Criteria (occasionality – usability, regularity – irregularity) of assignment – non-assignment of word-formation units to the structure of a typical word-building model were identified. The unique character of mutational word formation within the framework of verbal word production is noted, that, for example, cannot be said about substantive derivation. In the article complete and incomplete, redundant and defective derivational models are distinguished in accordance with the comparison of the composition of specific and typical derivational paradigms. It is concluded that a typical word-formation paradigm as a model dictates the possible limits within the framework of word formation of elements of a certain lexical-semantic group. Thereby it contributes to the stability of the derivational system by typing and, at the same time, prevents the implementation of the hidden potentialities of the language by ignoring the asystemic elements.